Toksoplasmosis pada Wanita Hamil - Risanto Siswosudarmo, Risanto Siswosudarmo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
A literature review of toxoplasmosis in pregnant women has been carried out. The airn..of this review is.to recognize the epidemiology, pathogenesis, mode of transmission, clinical manifestation, diagnosis and mariagernent. Toxoplasrnosis is a parasitic disease catiiedby ToxoplasinO gondii. Two groups of people being higly VuLnerable to the disease are the deieloping fetus and thoseWhO are inimtmodeficient. In humans, prevalence of positive serologic test titers increases with age. There are considerable differences in prevalence rate between, countries.. The prevalence rate of positive serologic test among pregnant women varies between 15% to 96% depending on the geographic area and age group, while the incidence of congenital toxoplasmosis varies from one to seven per 1000 live births.Toxoplasma invade every organ in the body; but the most vulnerable organ or tissue are those where access to circulating antibody is.impeded (e.g., brain and retina). The barrier to passive diffusiOn Of antibodies into brain and eye has been given as an explanatiOn of the continued proliferation of theparasite on theie sites at the same time that his disappearing from eirtraneural sites, giving rise to latent infection. The developing fetus is usually infected transplacentally. The risk of fetal infection is related to the time when maternal infection occurs. if Toxoplasma infection is acquired late in pregnancy, the protozoa are most frequently transmitted to the fetus but the infection is subclinical in the newborn. If, however, the mother is infected early in pregnancy (for example-during the third month) transmission to the fetus occurs less often but frequently results in severe disease to the new born. There is no clinical signs and symptoms pathognomonic for the disease in pregnant women. In the infant, there is usually a clinical triad Ã¢â¬â hydrocephalus, chorioretinitis and intracranial calcifications. However, definitive diagnosis of Toxoplasma infection is established by isolation of Toxoplasma gondii from blood or body fluid.,deniostration of cyst in the placenta or tissues or by serologic tests. Sulfonamides, pyrimethamine and spiramycine are drugs considered tole effective in killing the organism. Seronegative pregnant women is .the group of people in which avoidance of infectionKey Words: Toxoplasma gondii --pregnancy --congenital toxoplasmosis serologic test -- pyrimethamine